THE EFFECT OF HUMAN RESOURCES DEVELOPMENT ON EMPLOYEE WORK ACHIEVEMENT AT THE DEPARTMENT OF WATER RESOURCES, COPYRIGHT AND SPATIAL PLANNING GOVERNANCE OF NORTH SUMATRA PROVINCE - Zuleha - Gultom (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2021)
This research is entitled